Household goods and good households in late medieval London : consumption and domesticity after the plague - French, Katherine L. (Middle Ages series., 2021)
"Household Goods and Good Households in Late Medieval London looks at how increased consumption in the aftermath of the Black Death reconfigured long-held gender roles and changed the domestic lives of London's merchants and artisans for years to come."--